Antioxidant Properties of Roselle Vinegar Production by Mixed Culture of Acetobacter aceti and Acetobacter cerevisiae - Kongkiattikajorn , Jirasak (Agriculture and Natural Resources, 2014)
Roselle (Hibiscus sabdariffa) has been used in folk medicine and as a treatment for diseases and cancer. The objective of this study was to enhance the acetic acid production and the antioxidant activities (AOA) of Roselle vinegar using mixed culture fermentation. The Roselle wine was produced in a batch reactor. The kinetic parameters obtained for wine fermentation using Saccharomyces cerevisiae were: maximum ethanol production = 63.47 g.L-1, ethanol production rate = 2.25 g.L-1. hr-1, product (ethanol) yield coefficient = 0.45 and cell mass yield coefficient = 1.53. Using a mixed culture of Acetobacter aceti and Acetobacter cervisiae, the wine vinegar process optimization ranges for initial concentrations of ethanol and acetic acid as independent variables were 63.47 and 69.21 g.L-1, respectively. Roselle was processed into juice fermentation and vinegars. The total phenolics, total anthocyanins, and antiradical activity (1-1 diphenyl-2-picryl hydrazyl radical-scavenging (DPPH) method) were determined. Acetification increased the total anthocyanin content, total polyphenols and antioxidant activities. Correlations indicated that anthocyanins made greater significant contributions than did phenolics to the antioxidant activities of the products. The antiradical activity of wine from Roselle juice was high with an effective concentration which inhibited the DPPH activity by 50% (EC50) of 14.95 mg.L-1. The antioxidant activity of the vinegar product was high with an EC50 of 0.72 mg.L-1. The results indicated that fermentation is a better method for obtaining higher antioxidant activity of Roselle products. Furthermore, acetification significantly increased the anthocyanins and antioxidant activities.